Recent advances in hypervalent iodine(III)-catalyzed functionalization of alkenes - Li, Xiang; Chen, Pinhong; Liu, Guosheng (Beilstein Journal of Organic Chemistry, 2018)
Hypervalent iodine(III) reagents have been well-developed and widely utilized in functionalization of alkenes, however, generally either stoichiometric amounts of iodine(III) reagents are required or stoichiometric oxidants such as mCPBA are employed to in situ generate iodine(III) species. In this review, recent developments of hypervalent iodine(III)-catalyzed functionalization of alkenes and asymmetric reactions using a chiral iodoarene are summarized.
Keywords: asymmetric catalysis; functionalization of alkenes; hypervalent iodine(III)

The Organic Chemistry of Polycoordinated Iodine - Varvoglis, A. (VCH Publishers, Inc., 1992)

Chemistry of Hypervalent Compounds - Akiba, K.-y. (Wiley-VCH, 1999)

Chemistry of Hypervalent Compounds - Zhdankin, V. V.; Stang, P. J. (VCH Publishers, 1999)

Chemistry of Hypervalent Compounds - Ochiai, M. (VCH Publishers, 1999)

(untitled) - Varvoglis, A. (Tetrahedron, 2010)

Hypervalent Iodine Chemistry: Preparation, Structure and Synthetic Application of Polyvalent Iodine Compounds - Zhdankin, V. V. (John Wiley & Sons Ltd., 2014)

Iodine Chemistry and Applications - Kaiho, T. (John Wiley & Sons, Inc., 2015)

(untitled) - Wirth, T. (Top. Curr. Chem., 2003)

(untitled) - Merritt, E. A.; Olofesson, B. (Angew. Chem., Int. Ed., 2009)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2008)

(untitled) - Ochiai, M.; Miyamoto, K. (Eur. J. Org. Chem., 2008)

(untitled) - Dohi, T.; Kita, Y. (Chem. Commun., 2009)

(untitled) - Küpper, F. C.; Feiters, M. C.; Olofsson, B.; Kaiho, T.; Yanagida, S.; Zimmermann, M. B.; Carpenter, L. J.; Luther, G. W., III; Lu, Z.; Jonsson, M.; Kloo, L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Merritt, E. A.; Olofsson, B. (Synthesis, 2011)

(untitled) - Parra, A.; Reboredo, S. (Chem. – Eur. J., 2013)

(untitled) - Berthiol, F. (Synthesis, 2015)

(untitled) - Yoshimura, A.; Zhdankin, V. V. (Chem. Rev., 2016)

(untitled) - Muñiz, K. (Chem. Soc. Rev., 2004)

(untitled) - Donohoe, T. J.; Callens, C. K. A.; Flores, A.; Lacy, A. R.; Rathi, A. H. (Chem. – Eur. J., 2011)

Catalytic Heterofunctionalization - Togni, A.; Grützmacher, H. (Wiley-VCH, 2001)

(untitled) - Deprez, N. R.; Sanford, M. S. (Inorg. Chem., 2007)

(untitled) - Muñiz, K. (Angew. Chem., Int. Ed., 2009)

(untitled) - Xu, L.-M.; Li, B.-J.; Yang, Z.; Shi, Z.-J. (Chem. Soc. Rev., 2010)

(untitled) - Sehnal, P.; Taylor, R. J. K.; Fairlamb, I. J. S. (Chem. Rev., 2010)

(untitled) - McDonald, R. I.; Liu, G.; Stahl, S. S. (Chem. Rev., 2011)

(untitled) - Nicolaou, K. C.; Simmons, N. L.; Ying, Y.; Heretsch, P. M.; Chen, J. S. (J. Am. Chem. Soc., 2011)

(untitled) - Hara, S.; Nakahigashi, J.; Ishi-i, K.; Sawaguchi, M.; Sakai, H.; Fukuhara, T.; Yoneda, N. (Synlett, 1998)

(untitled) - Hara, S.; Nakahigashi, J.; Ishi-i, K.; Fukuhara, T.; Yoneda, N. (Tetrahedron Lett., 1998)

(untitled) - Kong, W.; Feige, P.; de Haro, T.; Nevado, C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Zhong, W.; Yang, J.; Meng, X.; Li, Z. (J. Org. Chem., 2011)

(untitled) - Tellitu, I.; Domínguez, E. (Tetrahedron, 2008)

(untitled) - Souto, J. A.; Martĺnez, C.; Velilla, I.; Muñiz, K. (Angew. Chem., Int. Ed., 2013)

(untitled) - Moriarty, R. M.; Khosrowshahi, J. S. (Tetrahedron Lett., 1986)

(untitled) - Romero, R. M.; Wöste, T. H.; Muñiz, K. (Chem. – Asian J., 2014)

(untitled) - Kohlhepp, S. V.; Gulder, T. (Chem. Soc. Rev., 2016)

(untitled) - Fuchigami, T.; Fujita, T. (J. Org. Chem., 1994)

(untitled) - Ochiai, M.; Takeuchi, Y.; Katayama, T.; Sueda, T.; Miyamoto, K. (J. Am. Chem. Soc., 2005)

(untitled) - Dohi, T.; Maruyama, A.; Yoshimura, M.; Morimoto, K.; Tohma, H.; Kita, Y. (Angew. Chem., Int. Ed., 2005)

(untitled) - Singh, F. V.; Wirth, T. (Chem. – Asian J., 2014)

(untitled) - Dohi, T.; Maruyama, A.; Takenaga, N.; Senami, K.; Minamitsuji, Y.; Fujioka, H.; Caemmerer, S. B.; Kita, Y. (Angew. Chem., Int. Ed., 2008)

(untitled) - Quideau, S.; Lyvinec, G.; Marguerit, M.; Bathany, K.; Ozanne-Beaudenon, A.; Buffeteau, T.; Cavagnat, D.; Chénedé, A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Fujita, M. (Tetrahedron Lett., 2017)

(untitled) - Yan, J.; Wang, H.; Yang, Z.; He, Y. (Synlett, 2009)

(untitled) - Zhou, Z.-S.; He, X.-H. (Tetrahedron Lett., 2010)

(untitled) - Alhalib, A.; Kamouka, S.; Moran, W. J. (Org. Lett., 2015)

(untitled) - Zhong, M.; Liu, S.; Yang, J.; Meng, X.; Li, Z. (Org. Lett., 2012)

(untitled) - Fujita, M.; Mori, K.; Shimogaki, M.; Sugimura, T. (Org. Lett., 2012)

(untitled) - Shimogaki, M.; Fujita, M.; Sugimura, T. (Eur. J. Org. Chem., 2013)

(untitled) - Fujita, M.; Yoshida, Y.; Miyata, K.; Wakisaka, A.; Sugimura, T. (Angew. Chem., Int. Ed., 2010)

(untitled) - Gelis, C.; Dumoulin, A.; Bekkaye, M.; Neuville, L.; Masson, G. (Org. Lett., 2017)

(untitled) - Uyanik, M.; Yasui, T.; Ishihara, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - Haubenreisser, S.; Wöste, T. H.; Martínez, C.; Ishihara, K.; Muñiz, K. (Angew. Chem., Int. Ed., 2016)

(untitled) - Uyanik, M.; Yasui, T.; Ishihara, K. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kang, Y.-B.; Gade, L. H. (J. Am. Chem. Soc., 2011)

(untitled) - Wöste, T. H.; Muñiz, K. (Synthesis, 2016)

(untitled) - Kong, A.; Blakey, S. B. (Synthesis, 2012)

(untitled) - Mizar, P.; Laverny, A.; El-Sherbini, M.; Farid, U.; Brown, M.; Malmedy, F.; Wirth, T. (Chem. – Eur. J., 2014)

(untitled) - Muñiz, K.; Barreiro, L.; Romero, R. M.; Martínez, C. (J. Am. Chem. Soc., 2017)

(untitled) - Yoneda, N. (J. Fluorine Chem., 2004)

(untitled) - Suzuki, S.; Kamo, T.; Fukushi, K.; Hiramatsu, T.; Tokunaga, E.; Dohi, T.; Kita, Y.; Shibata, N. (Chem. Sci., 2014)

(untitled) - Kitamura, T.; Miyake, A.; Muta, K.; Oyamada, J. (J. Org. Chem., 2017)

(untitled) - Mennie, K. M.; Banik, S. M.; Reichert, E. C.; Jacobsen, E. N. (J. Am. Chem. Soc., 2018)

(untitled) - Molnár, I. G.; Gilmour, R. (J. Am. Chem. Soc., 2016)

(untitled) - Banik, S. M.; Medley, J. W.; Jacobsen, E. N. (J. Am. Chem. Soc., 2016)

(untitled) - Woerly, E. M.; Banik, S. M.; Jacobsen, E. N. (J. Am. Chem. Soc., 2016)

(untitled) - Farid, U.; Malmedy, F.; Claveau, R.; Albers, L.; Wirth, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kitamura, T.; Muta, K.; Oyamada, J. (J. Org. Chem., 2015)

(untitled) - Banik, S. M.; Medley, J. W.; Jacobsen, E. N. (Science, 2016)

(untitled) - Liu, L.; Zhang, T.; Yang, Y.-F.; Zhang-Negrerie, D.; Zhang, X.; Du, Y.; Wu, Y.-D.; Zhao, K. (J. Org. Chem., 2016)

(untitled) - Shimogaki, M.; Fujita, M.; Sugimura, T. (J. Org. Chem., 2017)

(untitled) - Ngatimin, M.; Frey, R.; Levens, A.; Nakano, Y.; Kowalczyk, M.; Konstas, K.; Hutt, O. E.; Lupton, D. W. (Org. Lett., 2013)

(untitled) - Qurban, J.; Elsherbini, M.; Wirth, T. (J. Org. Chem., 2017)

(untitled) - Jobin-Des Lauriers, A.; Legault, C. Y. (Org. Lett., 2016)

(untitled) - Braddock, D. C.; Cansell, G.; Hermitage, S. A.; White, A. J. P. (Chem. Commun., 2006)

(untitled) - Braddock, D. C.; Cansell, G.; Hermitage, S. A. (Chem. Commun., 2006)

(untitled) - Ulmer, A.; Stodulski, M.; Kohlhepp, S. V.; Patzelt, P.; Pöthig, A.; Bettray, W.; Gulder, T. (Chem. – Eur. J., 2015)

(untitled) - Fabry, D. C.; Stodulski, M.; Hoerner, S.; Gulder, T. (Chem. – Eur. J., 2012)

(untitled) - Stodulski, M.; Goetzinger, A.; Kohlhepp, S. V.; Gulder, T. (Chem. Commun., 2014)

(untitled) - Li, M.; Yu, F.; Qi, X.; Chen, P.; Liu, G. (Angew. Chem., Int. Ed., 2016)

(untitled) - Li, M.; Yu, F.; Chen, P.; Liu, G. (J. Org. Chem., 2017)

(untitled) - Qi, X.; Yu, F.; Chen, P.; Liu, G. (Angew. Chem., Int. Ed., 2017)